Al-Islam is a religion of peace and harmony. - Muhammad Hadi Musholin Subagio (Jurnal Hikmatuna, 2015)
Islam is a religion that promotes peace and well-being for all people. It emphasizes the importance of seeking a peaceful life and discourages hostility among individuals. In Islam, a true believer is someone who ensures their own peace and well-being, as well as that of others. Throughout history, Islam has demonstrated its commitment to peace, such as through the Hudaibiyah treaty and the peaceful opening of Mecca. The caliph Umar ibn Abdul Aziz is renowned for his leadership in upholding peace and welfare for the people. To achieve a peaceful Islam, various approaches are advocated, including nurturing strong faith, fostering universal brotherhood, rejecting actions that cause chaos and harm, and promoting noble deeds that contribute to peace and well-being.